1995
DOI: 10.1002/hep.1840220511
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis and ulcerative colitis: Evidence for increased neoplastic potential

Abstract: Primary sclerosing cholangitis (PSC) is a biliary destructive disease mostly affecting patients with ulcerative colitis (UC). PSC has been suggested to be an independent risk factor for the development of colorectal malignancy in UC. Patients with PSC also have an increased risk of developing cholangiocarcinoma. This study aimed at assessing the cumulative risk of colorectal neoplasia in PSC and UC, and also to determine risk factors for the development of cholangiocarcinoma. Fifty-eight PSC patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
220
7
16

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(254 citation statements)
references
References 25 publications
11
220
7
16
Order By: Relevance
“…The cumulative risk of developing colorectal dysplasia/ cancer has been reported in a case-control study to be five times higher in patients with PSC plus ulcerative colitis compared with patients with ulcerative colitis alone after 20 to 25 years of ulcerative colitis duration. 45 A prospective study also found a significant increase in the development of dysplasia up to 9 years of follow-up in patients with ulcerative colitis and PSC (45%) compared with carefully matched controls with ulcerative colitis alone (16%). 61 Similarly, a historical cohort study found that dysplasia, as an indication for proctocolectomy, was significantly more common in the group of patients with ulcerative colitis and PSC compared with patients with ulcerative colitis alone.…”
Section: Malignancymentioning
confidence: 92%
See 2 more Smart Citations
“…The cumulative risk of developing colorectal dysplasia/ cancer has been reported in a case-control study to be five times higher in patients with PSC plus ulcerative colitis compared with patients with ulcerative colitis alone after 20 to 25 years of ulcerative colitis duration. 45 A prospective study also found a significant increase in the development of dysplasia up to 9 years of follow-up in patients with ulcerative colitis and PSC (45%) compared with carefully matched controls with ulcerative colitis alone (16%). 61 Similarly, a historical cohort study found that dysplasia, as an indication for proctocolectomy, was significantly more common in the group of patients with ulcerative colitis and PSC compared with patients with ulcerative colitis alone.…”
Section: Malignancymentioning
confidence: 92%
“…[41][42][43][44][45] The autopsy prevalence is much higher with cholangiocarcinoma, it being reported in 30% to 42% of patients with PSC undergoing autopsy. [45][46][47][48] Cholangiocarcinoma may develop in one third of patients with PSC if follow-up is extended long enough. 29 A large clinical experience has reported an annual incidence of less than 1%.…”
Section: Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of neoplasia in patients with IBD combined with PSC is controversial. Several studies have indicated that patients with IBD and PSC are at a higher risk of acquiring colorectal neoplasia [54][55][56][57], whereas larger studies from the Mayo clinic reported no risk [58] or only a borderline increased risk [59].…”
Section: Miscellaneous Risk Factors For Crc In Ibdmentioning
confidence: 99%
“…1 Worldwide, cholangiocarcinoma is associated with hepatolithiasis, liver fluke infestation, choledochal cysts, primary sclerosing cholangitis (PSC), and ulcerative colitis. 2,3 In Western countries, PSC is one of the main identifiable risk factors for the development of cholangiocarcinoma. 4 Presenting symptoms are often jaundice, pruritus, weight loss, anorexia, and vague abdominal discomfort.…”
mentioning
confidence: 99%